Abundant Solutions of Distinct Physical Structures for Three Shallow Water Waves Models - Wazwaz, Abdul-Majid (Discontinuity, Nonlinearity, and Complexity, 2026)
In this work, we investigate three completely integrable model equations used to describe shallow water waves. A variety of techniques will be sued to determine abundant solutions, of distinct physical structures, for each model. The three models give soliton solutions, periodic solutions, rational hyperbolic functions and rational solutions as well.